Reporting verb variation across disciplines: An academic corpus study - Eckstein, Grant; Rawlins, Jacob; Taylor, Hannah; Briggs, Haley; Candland, Andrea; Hanks, Elizabeth; Hill, Sarah (Journal of Academic Language and Learning, 2022)
Reporting verbs are used in academic writing to establish authorial voice when referencing previous research. Although the practice is widespread, inexperienced academic writers and second-language learners may struggle to select appropriate reporting verbs within their given discipline or may overuse them in ways that signal outsider status. The present study explores the distribution of reporting verbs across six disciplines in a corpus containing 270 academic research background sections (introduction and literature review). The results illustrate that disciplines vary widely in the number and type of reporting verbs used. While common reporting verbs across disciplines include argue, examine, report, show, suggest, and use, most disciplines utilize a large number of reporting verbs that are unique only to a specific discipline. The findings reported from this study, as well as the verb lists, can be used by teachers and English language learners to expand or establish authorial voice in a way that replicates disciplinary in-group status.